METODOLOGI PENGEMBANGAN LIVING HADITS DALAM PENDIDIKAN ISLAM - Abda Billah Faza MB (IAIN Purwokerto, 2019)
This reserch investigates about living hadith that's created through Islamic education. Study about living hadith is a new branch prefield of hadith science. This study is still limited it self on social-empiric in society, and not to take wider on educational sphere. Islamic education that purposed to educate the nation also to build students with Islamic tenets be from al Qur'an and al Hadith that certainly always changes to new study. This study try to integrate both lines of science and also to open new study in living hadith research which usually conducted by student of Hadith Science Faculty and Education Faculty to fulfill their last task as an undergraduate, graduate or postgraduate students. Because the research of living hadith always studied about the culture with in the society, yet researcher use the literatures as object of study. Then the researcher analyze the literatures either journals of education, living hadith and social; and also books related. After that, the researcher inferred that there is a relation among social, living hadith and education. The research proved that study of living hadith that similiar to social-culture life can be developed through education. It caused by the relevance between education and the social-culture which developed in the society. Educational process included of goals, visions, missions and methods is always adopted from the condition of social-culture existing in the society. Furthermore, the study about living hadith is not only investigating the existed thing but also can be developed through Islamic education by research and development methodology.